Nanoneuroprotection and nanoneurotoxicology - Sharma, H. S. (Hari Shanker); Sharma, Aruna, MD (Progress in brain research, 2019)
Nanoneuroprotection and Nanoneurotoxicology, Volume 245 of the Progress in Brain Research series, deals with recent developments in the field of neurotoxicity and neuroprotection using nanobiotechnology for the first time. Chapters in this updated release include Sleep deprivation induced brain pathology and concussive head trauma-Neuroprotective effects of nanowired delivery of drugs and hormones, Nanomedicine in Alzheimer's Disease: amyloid beta targeting strategy, How traumatic brain injury alters amino acids balance in the central nervous system-Neuroprotection by TiO2 nanowired delivery of drugs and antibodies, Nanowired delivery of DL-3-n-butylphthalide and neuroprotection in concussive head injury, Nanodelivery of drugs and antibodies for superior neuroprotection in Alzheimer's disease, and more. Key Features: Highlights recent development in nanopharmacetical research with reference to brain disease; Provides new insights on the possible role of nanomaterials and their pronounced effects on CNS injury or repair. Readership: Researchers and students of neuroscience, psychology, and the biological sciences interested in nanoneuroprotection and nanoneurotoxicology. --